To what extent has micro-financing been impactful in reducing gender-related inequalities in India? - Aayush Garg (Innovative Research Thoughts, 2023)
In 2019, India was ranked 123rd on the Gender Inequality Index (GII) with a score of 0.488, and it grappled with a significant gender gap in its labor force participation, amounting to 55.9% ["Gender Inequality Index" data]. Women in India encountered substantial levels of structural violence, defined as violence stemming from societal structures that perpetuate oppression [Heywood, 426]. This took various forms, including traditional constraints on education and employment opportunities, poverty, and physical, sexual, and emotional violence. These factors resulted in an unequal distribution of power, compelling women to assume subordinate roles in society and hindering their ability to achieve equal status, authority, and prosperity in the long run [Singh and Singh]. Postcolonial feminists often argue that women can play pivotal roles in development and poverty reduction initiatives, provided they are given local ownership and the opportunity to defy stereotypes portraying them as disempowered, impoverished, and under-educated [Heywood, 437]. One model that aligns with this vision is microfinance, which establishes self-help groups and offers access to loans for low-income families, enabling them to establish small businesses or enhance agricultural projects. To explore the extent of microfinance's impact in reducing gender-related inequalities in India, this report conducts a series of interviews with experts in the field.